Multi-level governance in public transport: Governmental layering and its influence on public transport service solutions. (September 2018) - Veeneman, Wijnand; Mulley, Corinne
Abstract: Public transport is supported by governments to deliver social and environmental objectives through public value established through the instrument of a subsidised transport services for its inhabitants and visitors. In the current literature on public transport policy and governance, governments are generally seen as singular: the transport authority or the government. However, as has been well researched in administrative science, governments are not as singular and not as unitary as assumed by this literature. Different governments in an area operate on various scales of jurisdictions and their actions in a specific policy field are generally mutually dependent. These different levels of government do not necessarily coordinate their policies, as the scale differences drive different perspectives and objectives. This is conceptualised as multi-level governance with documented issues and practices that resonate in the provision of urban public transport. This paper presents the literature context of multi-level governance and its application to public transport provision through the examination of case studies. The hypothesis that the distribution of agency (decision power) and funding has a great deal of explanatory power for the public transport solutions that are implemented is examined in the context of case studies in the Netherlands, Australia and South Africa. These seek to demonstrate how the distribution of agency and funding over different layers of government explain the directions in which public transport service solutions have developed in recent times.